Pengaruh Implementasi Aplikasi Keuangan Berbasis Digital Terhadap Optimalisasi Kinerja UMKM Di Kecamatan Medan Johor - Izzati, Nadhila; Kurnia Ningsih, Heny Tri Astuti; Khairani Lubis, Farida (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2025)
This study aims to investigate the impact of digital financial application usage on the performance of micro, small, and medium enterprises (MSMEs) in the Medan Johor District. A quantitative research design was adopted, utilizing a survey as the primary data collection method. Data were gathered using purposive sampling by distributing questionnaires to MSME operators who utilize the